Mechanical jejunal obstruction caused by a migrated intragastric balloon: a case report - Mohamed S Ghali (22225471) (2024)
An intragastric balloon is often used as a temporary solution for weight loss. It is endoscopically placed into the stomach and filled with air or saline to encourage fullness and reduce meal intake. A 23-year-old female with a history of a gastric balloon procedure presented to the emergency department with generalized abdominal pain and recurrent vomiting. Initial imaging with ultrasound and computed tomography scans revealed a collapsed migrated gastric balloon causing a small bowel obstruction. Despite initial conservative management, the patient required surgical intervention, which involved laparoscopic exploration, mini laparotomy, and enterotomy to extract the migrated balloon. Postoperatively, the patient had an uneventful recovery and was discharged with a stable condition. This case underscores the importance of considering device-related complications in patients with gastric balloons presenting with gastrointestinal symptoms and highlights the need for prompt imaging and appropriate surgical management. Intragastric balloon migration leading to small bowel obstruction is a rare but serious complication that should be considered in patients presenting with abdominal pain and vomiting following a gastric balloon procedure. Prompt imaging and surgical intervention are crucial for effective management and favorable outcomes. Other Information Published in: Journal of Surgical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jscr/rjae744